Diversity and Plant Growth Promoting Activities of Actinomycetes from Mangroves - Paweena Suksaard (Science Faculty of Chiang Mai University, 2019)
Four hundred forty eight actinomycetes were isolated from water and sediment samples of mangrove areas at Andaman Coastal Research Station for Development of Kasetsart University Research and Development Institute, Ranong province, Thailand. According to the morphological characteristics and occurrence of diaminopimelic acid (DAP) isomeric form in the cell hydrolysates, 318 isolates of actinomycetes were clustered as members of streptomycete and 130 isolates were clustered as non-streptomycete type. These 448 isolates could be separated into 8 spore-colour groups and 16S rRNA gene sequences of 146 representative isolates, which had different morphologies from each colour group, were analyzed. They were classified into 14 genera: Actinomadura, Actinoplanes, Gordonia, Isoptericola, Jiangella, Microbispora, Micromonospora, Nocardia, Nocardiopsis, Nonomuraea, Pseudonocardia, Saccharopolyspora, Streptomyces and Streptosporangium. Streptomyces was most prevalent genus with 65.1 % occurrence frequency followed by Micromonospora (6.8 %), Nonomuraea (6.2 %) and Saccharopolyspora (6.2 %). Assessment of plant growth promoting activities of the 448 isolates exhibited that 88.4 %, 50.9 % and 38.8 % of them possessed indole-3-acetic acid (IAA), siderophores and phosphate solubilizing activities, respectively. Fifty potent isolates for plant growth promoting activities were further screened for their antagonistic potential against rice pathogenic bacteria (Xanthomonas oryzae pv. oryzae and X. oryzae pv. oryzicola) and aminocyclopropane carboxylate (ACC) deaminase production. Fourteen isolates inhibited both pathogens and 11 isolates exhibited ACC-deaminase activity. Isolates 1SM5-02, 2SH3-07, 3SH5-05 and 3WH5-01 exhibited high plant growth promoting activities even up to 300 mM of NaCl stress. Their 16S rRNA gene sequences were closely related to Nocardiopsis yanglingensis A18T (98.85 %), Streptomyces jiujiangensis JXJ 0074T (99.35 %), Streptomyces psammoticus NBRC 13971T (99.51 %) and Pseudonocardia oroxyli D10T (99.78 %), respectively. The four isolates significantly enhanced shoot and root weight and root length of rice seedling under non-saline and up to 200 mM NaCl conditions. This is the first report on diversity and plant growth promoting potentials of actinomycetes in mangrove from Ranong province, Thailand.